Spectrum of cytological finding in superficial lymphnode enlargement in a tertiary care center-retrospective study - Dr. T. Elavarasan; Dr M. S Shruthi; Dr R. D. Puvitha (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Lymphadenopathy refers to lymph nodes that are abnormal in size, consistency or number. It is one of the commonest and significant clinical presentations of patients, attending the outdoor clinics in most hospitals. Superficial lymphadenopathy ranked among the most common clinical findings encountered in the etiology of lymph nodes enlargement range from spectrum of infections, reactive hyperplasia to malignant diseases. Diagnosing these lesions poses a major challenge to the clinicians. FNAC is an easy, safe, reliable, rapid and inexpensive method for diagnosing enlarged lymph nodes with a high degree of accuracy. The aim of our study is to study and evaluate the spectrum of cases of superficial lymph node enlargement in our region.Materials and methods: The retrospective study was done in the cytological section of the department of pathology in our hospital over a period of two years. Patients who visited the OPD of our hospital, with complaints of lymph node enlargement weresent for FNAC for proper diagnosis. The data were retrieved, compiled, summarized and statistically analyzed.Results: Of the 770 cases studied, the most common cause of lymphadenopathy was reactive lymphadenitis with 438 cases (56.8%). The next common diagnosis was found to be granulomatous lymphadenitis with 197 cases (25.5%) followed by suppurative lymphadenitis in 68 cases (8.8%), metastatic lymphadenopathy in 61 cases(7.9%) and malignant lymphoma in 6 cases (0.7%).Conclusion: FNAC is an easy, simple, safe and inexpensive method of diagnosing lymph node lesions.